Optimization driven model-space approach for gas clouds using full waveform inversion - Prajapati, S. (Society of Petroleum Engineers, 2014)
Exact quantitative information from seismogram based on full-wavefield modeling with non-linear wave equation method enhanced by computational cost and time over-burden, conventional full waveform inversion (FWI) method is a very challenging. Due to the limited accuracy, lack of adequate and accurate initial velocity model, and the approximate modeling of the wave-physics complexity, local minima does not prevent towards the convergence of misfit function. An alternative simultaneous-source encoding inversion technique is proposed. With the use of proposed algorithm, successfully recoverd the true geological information though inversion, however, the use of simultaneous source introduces the crosstalk artifacts which are efficient at higher frequencies and minimum at low frequencies, which we can clearly see in the model fit at top but it has minimal effect on whole dataset. However, we successfully recovered the true geological structure. Copyright Â© 2014, International Petroleum Technology Conference.